RFC1 repeat expansions: A recurrent cause of sensory and autonomic neuropathy with cough and ataxia. (23rd March 2022) - Beijer, Danique; Dohrn, Maike F.; De Winter, Jonathan; Fazal, Sarah; Cortese, Andrea; Stojkovic, Tanya; Fernández‐Eulate, Gorka; Remiche, Gauthier; Gentile, Mattia; Van Coster, Rudy; Dufke, Claudia; Synofzik, Matthis; et al.
Abstract: Background and purpose: Ataxia and cough are rare features in hereditary sensory and autonomic neuropathies (HSAN), a group of diseases of mostly unknown genetic cause. Biallelic repeat expansions in RFC1 are associated with cerebellar ataxia, neuropathy, and vestibular areflexia syndrome (CANVAS). This study aimed to investigate the prevalence of RFC1 repeat expansions in a cohort of HSAN patients. Methods: After unremarkable whole‐exome sequencing (WES) analysis, we performed repeat‐primed PCR to detect intronic RFC1 expansions in 12 HSAN families, who all presented with chronic cough. Results: In these patients, 75% carried biallelic expansions of the pathogenic AAGGG motif. Compared with RFC1 −/− cases, RFC1 +/+ cases presented more consistently with positive sensory and autonomic symptoms. Afferent ataxia was more severe in the RFC1 +/+ cohort and cerebellar ataxia was a common feature (21%). Conclusions: We demonstrate that RFC1 is a frequent cause of (WES‐negative) HSAN with chronic cough and ataxia. The diagnostic yield of RFC1 repeat‐primed PCR was surprisingly high, given that HSAN is genetically poorly understood. This combination of HSAN, ataxia, and chronic cough symptoms represents a new nosological entity within the neuropathy‐ataxia spectrum. Abstract : RFC1 expansions are a frequent cause of whole‐exome sequencing‐negative hereditary sensory and autonomic neuropathies (HSAN) with chronic cough. The diagnostic yield of RFC1 repeat‐primed PCR was surprisingly high, given that HSAN is genetically poorly understood. This combination of HSAN, ataxia, and chronic cough symptoms represents a new nosological entity within the neuropathy‐ataxia spectrum.